Timing and Duration of Observation Periods of Foraging Behavior in Natural Grasslands - Jochims, Felipe; Soares, Émerson Mendes; de Oliveira, Leandro Bittencourt; Kuinchtner, Bruno Castro; Casanova, Pedro Trindade; Marin, Luciana; de Quadros, Fernando Luiz Ferreira (Frontiers in Veterinary Science, 2020)
The goals of this study were to evaluate the length of time grazing which should be monitored over a 24-h period to predict the grazing behavior of beef heifers within a season and determine the patterns of foraging activity over 24 h. A database was constructed between 2010 and 2012 for beef heifers managed under rotational grazing in a natural grassland. Grazing, rumination, and other activity times were assessed visually during 24 h on 15 occasions. Data were classified according to climatic seasons, generating 12 replicates in summer, 18 in spring, 24 in autumn, and 36 in winter. Treatments were the evaluation of four distinct periods: from sunrise to sunset (DAY-SUN), daylight duration from dawn to nightfall (DAYLIGHT), DAYLIGHT plus 2 h (DAYLIGHT+2), DAYLIGHT to midnight (DAYLIGHT to 0), and the entire 24 h period (CONTROL). Differences for grazing, rumination, and other activities were found in all seasons for the evaluation periods. Sampling sufficiency was reached only with the DAYLIGHT to 0 and CONTROL for all four climatic seasons. The DAYLIGHT to 0 treatment covered 75% of a 24-h period and 95% of the mean foraging time took place during this time interval. Considering grazing distribution during a day, in the warm seasons, the major grazing period during mornings occurred earlier than in the cool seasons, and in cool seasons, the grazing peak was observed during the afternoon. Visual observations from dawn until midnight represented the total grazing time and natural behavior of heifers and could be used to represent grazing activities for the entire day.